Uji potensi bioherbisida ekstrak daun nambu betung (dendrocalamus asper) dalam menghambat pertumbuhan cyperus rotundus L. - Dita Prihartini; Gita Nabila Islami (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Weeds are undesirable plants that can reduce the productivity of cultivated crops; therefore, effective control measures are required. This study aimed to analyze the effect of Dendrocalamus asper leaf extract as a bioherbicide on the growth of nutgrass (Cyperus rotundus L.), as well as to evaluate the effect of different extract concentrations under field conditions. The experiment was arranged using a Completely Randomized Design (CRD) with five levels of bamboo leaf extract concentrations: 0 g/mL, 0.17 g/mL, 0.42 g/mL, 0.81 g/mL, and 1.5 g/mL. The observed data were analyzed using Analysis of Variance (ANOVA), followed by the Least Significant Difference (LSD) test when significant differences were detected. The results showed that the application of D. asper leaf extract inhibited the growth of C. rotundus in terms of plant height, leaf number, stem diameter, and root length. The lowest inhibition was observed at a concentration of 0.42 g/mL, while the highest inhibition occurred at 1.5 g/mL. Similarly, for fresh and dry weight parameters, the extract demonstrated inhibitory effects on weed growth. The lowest inhibition was found at 0.17 g/mL, whereas the highest inhibition was consistently observed at 1.5 g/mL. These findings indicate that the application of D. asper leaf extract contributes to a reduction in the water content of C. rotundus, suggesting its potential as a natural bioherbicide.